Persepolis The Story of a Childhood - Satrapi Marjane (Pantheon Books, 2003)
In 1970s Iran, Marjane 'Marji' Statrapi watches events through her young eyes and her idealistic family. Their long dream is realized when the hated Shah is defeated in the Iranian Revolution of 1979. Now ruled by Islamic fundamentalists, Marji grows up to witness firsthand how the new Iran has become a repressive tyranny on its own. With Marji dangerously refusing to remain silent at this injustice, her parents send her abroad to Vienna to study. This change proves an equally difficult trial for Marji and finds herself in a different culture loaded with abrasive characters and profound disappointments that deeply trouble her. Even when she returns home, Marji finds that both she and her homeland have changed too much and the young woman and her loving family must decide where she truly belongs.